2015
DOI: 10.1007/s10238-015-0377-y
|View full text |Cite
|
Sign up to set email alerts
|

HFE p.C282Y gene variant is associated with varicose veins in Russian population

Abstract: Recently, the association of polymorphism rs1800562 (p.C282Y) in the hemochromatosis (HFE) gene with the increased risk of venous ulceration was shown. We hypothesized that HFE gene polymorphism might be involved not only in ulceration process, but also in susceptibility to primary varicose veins. We genotyped HFE p.C282Y (rs1800562) and p.H63D (rs1799945) variants in patients with primary varicose veins (n = 463) and in the control group (n = 754). In our study, p.282Y variant (rs1800562 A allele) was signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 46 publications
(48 reference statements)
0
22
0
2
Order By: Relevance
“…Association with red blood cell traits is intriguing. Hypothetically, both erythrocyte homeostasis and VVs could be linked to iron overload 19,20 . It is noteworthy that association between hemochromatosis-related functional variant in the HFE gene and primary VVs was revealed in our previous candidate-gene study in ethnic Russian individuals 19 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Association with red blood cell traits is intriguing. Hypothetically, both erythrocyte homeostasis and VVs could be linked to iron overload 19,20 . It is noteworthy that association between hemochromatosis-related functional variant in the HFE gene and primary VVs was revealed in our previous candidate-gene study in ethnic Russian individuals 19 .…”
Section: Resultsmentioning
confidence: 99%
“…Other prioritized genes were PPP3R1, EBF1, STIM2 , and HFE . The latter gene has been linked to the risk of VVs in our recent candidate-gene study 19 . Meanwhile, we could not prioritize any gene in the locus tagged by rs3101725.…”
Section: Discussionmentioning
confidence: 97%
“…Several common polymorphisms of the HFE gene, such as C282Y (rs1800562), H63D (rs1799945) and S65C (rs1800730), have been reported [ 18 , 19 ]. Accumulating evidence indicates that HFE mutations are associated with susceptibility to many clinical diseases, such as Parkinson's disease (PD) [ 20 ], primary varicose veins [ 21 ] and coronary heart disease (CHD) [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…In further agreement with advocating a more individualised approach to management of CVD, the specialists also found consensus on statement 10 regarding the utility of identifying genetic polymorphisms that may affect progression of CVD. Indeed, several polymorphisms have been identified that appear to stratify with disease, notably HFE p.C282Y as well as those in metalloproteases [57][58][59][60]. Other researchers have proposed that a genetic risk score might be useful in distinguishing patients at risk for more severe disease [61].…”
Section: Conservative Therapymentioning
confidence: 99%